OPTIMIZING OF COMPOSITE BOARD PRODUCTION MADE FROM WOOD WASTE AND BAMBOO - Sukma Surya Kusuma; Bambang Subiyanto; Muh Yusram Massijaya (Widyariset, 2011)
The objective of this research was to develop composite board made of bamboo veneer, rubber wood veneer, and log core waste of rubber wood with determining optimum log core strip constructions and type of veneers. The bamboo veneer made from slices of Betung (Dendrocalamus asper), Andong (Gigantochloa verticilata), and Tali (Gigantochloa apus) bamboo species. Strip forms of log core were square and silindric forms. Arrangement of log core strip was zigzag in design. Composite boards were constructed from seven layers. Water Based Polymer Isocyanate was used as adhesive in composite board productions. The research results showed that the composite board made of Andong bamboo veneer, and square strip of log core performed best quality compared to other composite boards. The above type of composite boards fulfi lled Japanese Agricultural Standard (JAS) No. 1516, 2003 for structural plywood. These composite board was suitable for structural purposes.